İnternet aracılığı ile işlenen suçlar - Çekiç, Burak (My University, 2006)
İNTERNET ARACILIĞI İLE İŞLENEN SUÇLAR Türk hukukunda “bilişim suçları” ile ilgili ilk düzenleme 1989 TCK Öntasarısında yer aldı. Öntasarıda meydana getirilen ufak değişikliklerle 1991 yılında 3756 sayılı yasayla TCK’na Onbirinci Bab olarak eklendi. 5237 sayılı Türk Ceza Yasasında ise konuyla ilgili düzenlemelere Bilişim Alanında Suçlar Bölümünde daha geniş bir şekilde yer verildi. Söz konusu çalışma, bilgisayar, bilişim sistemleri ve internet kavramları ile Türk Ceza Hukukunda bilişim suçlarına ilişkin yapılan düzenlemeleri ele almayı amaçlamaktadır. TCK’nın 243., 244. ve 245. maddeleri, FSEK’in 71., 72., 73. ve 74 maddeleri, EİK’nın 16. ve 17. maddelerinde tanımlanan bilişim suçları ile Türk Ceza Hukukunda düzenlenen yazılı, sözlü veya yayın yoluyla işlenebilen suçlar inceleme konusunu oluşturmaktadır.

CRIMES COMMITTED USING THE INTERNET First regulation of computer crimes in Turkish Criminal Law is placed at 1989 Turkish Penal Code Draft Law. In 1991, Computer crimes, added to the Turkish Penal Code, with 3756 numbered Act. Finnaly it is placed at 5237 numbered new Turkish Penal Code in section informatics related crimes. In this study, I tried to research computers, informatics systems, internet concepts and regulations about computer crimes at Turkish Criminal Law. Turkish Penal Code’s (TCK) 243., 244., 245. articles. Turkish copyright is protected by Fikir ve Sanat Eserleri Kanunu (FSEK) that was accepted in 1951. This law includes subject of scientific and literature publications (including computer software), music, fine arts productions, movies and gives the rights to right holders of these productions in these subjects as spiritual and financial. This law has been amended in 1983 and 1995. Last change of it has been done in 3rd March 2001. Those changes were on developed and changed forms of productions with infomation technologies. In this study, I tried to research digital signatures regulations at Electronical Signature Law.
Keywords: Hukuk; Kamu Hukuku; Suçlar_İnternet